Early Childhood Development in Cape Verde and Guinea - Jaramillo, A.; Tietjen, K. (2012)
The note explores the need to identify both cost effective, and adaptable interventions in the promotion of early childhood care and education (ECCE) programs, to benefit communities, and countries at large. To this end, based on a Bank sector study that examines such programs in Cape Verde, as a relatively wealthy African country, and in comparison Guinea, as a relatively poor country, it is emphasized that the feasibility of different approaches may be country specific. The study questions the overall status, and profile of early childhood development programs, and the factors determining child enrollment in pre-school programs, as well as the extent of influence of pre-school attendance in child development. It also reviews the program characteristics, seemingly effective in terms of child development, including the policy implications of these programs in terms of costs, financing, and implementation. Findings, and recommendations suggest that pre-school education can be a double-edged sword, that can both alleviate, and exacerbate disparities, while wide variations in pre-school effectiveness indicate the many factors influencing its success. But government plays a critical role in supporting ECCD programs, that is, it can improve efficiency, and equity. Highlights feature longer-term impact of pre-school for primary school performance, and how to best expand access to pre-school, without raising public expenditures.